„KOSOVO“ BY BRANISLAV NUŠIĆ, LAND OF HEAVEN AND EARTH: FROM DEMOGRAPHIC-ETNOGRAPHIC PICTURE TO NATIONAL-IDEOLOGICAL (RE)INTERPRETATION OF TRADITION - Peric, Dragoljub (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
The paper aims to show what Nušić’s intentions were in writing this unusual documentary demographic-ethnographic book about Kosovo and Metohija. At the centre of this cultural and folkloric-rhetorical interpretation is the legend about the (first) Battle of Kosovo, as well as the ways explored by the author to select and represent particular motifs from the legend of the Battle of Kosovo. The analysis shows that the territory of Kosovo and Metohija, in Nušić’s opinion, is not only the territory that covers the historical core of the feudal Serbian country (Old Serbia), or the geographical zone located on the periphery of the crumbling Ottoman Empire during the last decade of the 19th century, which records the increasing migratory movements of the Serbian population towards the Kingdom of Serbia. It is not only the spiritual and physical homeland of our ancestors, nor is it simply an area of the centuries-old Serbian cultural heritage. It is all of this at the same time. In this context, to the author, the Kosovo legacy, Lazar’s sacrifice, Miloš’ feat, for example, represent the embodiments of the Christian archetype of the martyr and an exemplary model of heroism, valued by the price of life laid down for the freedom of one’s own people. The folklore narrative, supported by material evidence and based on the rhetorical strategy of credibility, joined and connected through the legend about the Battle of Kosovo, to Branislav Nušić, becomes the national and identity-defining category.
Keywords: legend about Battle of Kosovo, folklore, mythical narrative, ideology, rhetorical interpretation, trustworthiness, rhetoric of truth, Serbian national identity